The Analysis of Factors Related to Creativity in the Sample of Physical Education Teachers (Baltic Journal of Sport and Health Sciences, 2012)
Research background and hypothesis. There are many obstacles for creativity in physical education teachers’ work  but  majority  of  physical  education  teachers  tend  to  work  creatively  so  it  is  worthwhile  to  explore  which variables predict creativity. The hypothesis of the study: Personal factors are more important for physical education teachers’ creativity in comparison to social factors.Research  aim  was  to  identify  individual  and  social  factors,  predicting  creativity  in  the  sample  of  physical education teachers. Research methods. Quantitative study. The questionnaire survey was used to establish the level of creativity, creative self-efficacy, motivation, emotions and the microclimate characteristics. The sample involved 120 physical education teachers. Research results. Creativity was predicted by self-efficacy and intrinsic process motivation. Extrinsic motivation inhibited creativity in physical education teachers’ work. Supervisory encouragement for creativity has the only social factor facilitating creativity.Discussion and conclusions. The obtained data confirmed interrelation between creativity and self-efficacy and validated results obtained by D. F. De Moulin (1993). Intrinsic process motivation also predicts creativity. It is in agreement with Y. Ommundsen and S. Eikanger Kvalo’s (2007) results. Extrinsic motivation has negative impact towards  creativity.  It  is  possible  that  teachers  motivated  intrinsically  create  task-involving  motivational  climate which leads to competitiveness (Ommundsen, Eikanger Kvalo, 2007). Supervisory encouragement is the only social variable predicting teachers’ creativity. The data revealed that supervisors’ behavior was more important than that of colleagues (Laker et al., 2008; Blankenship, Coleman, 2009).Keywords: creativity, personal and social factors.